2017
DOI: 10.1177/0309133317714247
|View full text |Cite
|
Sign up to set email alerts
|

Tree growth across the Nepal Himalaya during the last four centuries

Abstract: The climate of Nepal has changed rapidly over the recent decades, but most instrumental records of weather and hydrology only extend back to the 1980s. Tree rings can provide a longer perspective on recent environmental changes, and since the early 2000s, a new round of field initiatives by international researchers and Nepali scientists have more than doubled the size of the country’s tree-ring network. In this paper, we present a comprehensive analysis of the current tree-ring width network for Nepal, and us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 67 publications
2
17
0
Order By: Relevance
“…Our results indicate that large volcanic events may reduce moisture availability in the central Himalayas. These findings support early work using a tree-ring width network developed from 11 tree species in Nepal where widespread growth suppressions were evident in the early 1800s [28]. These growth suppressions corresponded with the most severe drought in our reconstruction that occurred from 1809À1823.…”
Section: Coupling Between Drought and Large Tropical Volcanic Eruptionssupporting
confidence: 89%
“…Our results indicate that large volcanic events may reduce moisture availability in the central Himalayas. These findings support early work using a tree-ring width network developed from 11 tree species in Nepal where widespread growth suppressions were evident in the early 1800s [28]. These growth suppressions corresponded with the most severe drought in our reconstruction that occurred from 1809À1823.…”
Section: Coupling Between Drought and Large Tropical Volcanic Eruptionssupporting
confidence: 89%
“…The inter-series correlation and SNR for this study were higher compared to previous studies of the same species [21,[33][34][35], indicating the robustness of our chronology. Similar to most of the tree-ring-width chronologies in Nepal [19,53,54], we also observed a significant growth depression during the 1810s, followed by a distinct increase in growth since 2003 CE. Thapa et al [54] developed a composite chronology combining 55 tree chronologies from Nepal and mentioned these growth fluctuations as a major milestone for Nepalese tree-ring chronologies regardless of the tree species.…”
Section: Characteristics Of the Timang T Dumosa Chronologysupporting
confidence: 84%
“…Similarly, Dawadi et al (2013) also observed fluctuation in the growth of B. utilis over the past 400 years in the Langtang region. Similarly, Thapa et al (2017) also reported increasing or decreasing growth trend in different chronologies from Nepal Himalaya. The differences between the growth trends in the present study and the previous studies could be due to the differences in the species, site conditions as well as methods used to detrend the raw tree-ring series, and the type of chronologies.…”
Section: Figure 4 : the Residual Ring-width Chronology Of Abies Spectmentioning
confidence: 77%
“…So, inspecting fire-scarred trees dated with dendrochronological techniques will be reliable method for providing quantitative information on fire-regime evidence at multiple scales to study fire events, their frequency, severity and patterns even on remote geographical area. Though several tree-ring related studies have been carried out in Nepal (Cook et al, 2003;Chhetri and Thapa, 2010;Gaire et al, 2011Gaire et al, , 2014Gaire et al, , 2016 but study regarding the fire disturbances in the perspective of dendroecology is still lacking in the whole country (Gaire et al, 2013;Thapa et al, 2017). So this study will help to inform management, and provide insight into the effects of fire on study area.…”
Section: Fire History and Climate-growth Response Of Abies Spectabilismentioning
confidence: 94%